Respuesta :

Answer:

[tex](x,y) = (-1,0)[/tex]

Step-by-step explanation:

Given

[tex](x+1)^2 = -8(y-2)[/tex]

Required

The coordinates of the focus

First, write the expression in form of: [tex]y=a(x-h)^2+k[/tex]

[tex](x+1)^2 = -8(y-2)[/tex]

[tex](x+1)^2 = -8y + 16[/tex]

[tex]-8y + 16 = (x+1)^2[/tex]

Subtract 16 from both sides

[tex]-8y = (x+1)^2 - 16[/tex]

Divide through by -8

[tex]y = -\frac{1}{8}(x+1)^2 - \frac{16}{-8}[/tex]

[tex]y = -\frac{1}{8}(x+1)^2 +2[/tex]

In this case:

[tex]a = -\frac{1}{8}[/tex]

[tex]-h = 1[/tex]         [tex]h = -1[/tex]

[tex]k = 2[/tex]

The focus of the parabola is:

[tex](x,y) = (h,k + \frac{1}{4a})[/tex]

This gives:

[tex](x,y) = (-1,2 + \frac{1}{4*-\frac{1}{8}})[/tex]

[tex](x,y) = (-1,2 + \frac{1}{-\frac{1}{2}})[/tex]

[tex](x,y) = (-1,2 -2)[/tex]

[tex](x,y) = (-1,0)[/tex]

ACCESS MORE